If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-14=8(y+5)-2y
We move all terms to the left:
-14-(8(y+5)-2y)=0
We calculate terms in parentheses: -(8(y+5)-2y), so:We get rid of parentheses
8(y+5)-2y
We add all the numbers together, and all the variables
-2y+8(y+5)
We multiply parentheses
-2y+8y+40
We add all the numbers together, and all the variables
6y+40
Back to the equation:
-(6y+40)
-6y-40-14=0
We add all the numbers together, and all the variables
-6y-54=0
We move all terms containing y to the left, all other terms to the right
-6y=54
y=54/-6
y=-9
| 192=-8(8+8x) | | 24-2=8(p+8) | | 0.10(y-2)+0.18y=0.08y-1 | | 1.2y+0.25=7 | | 139-w=264 | | 4(6x-5)=172 | | -v+24=232 | | 2x-52.2=90 | | 2x-16+x=2;6 | | +3x-3x=0 | | 201+-w=96 | | -17-5k=-2k+7(5+7k) | | 4x+7=7x•14 | | -12=-2(c-9) | | 9-m=-5m+1 | | ½=2x | | –10p−5=–9p | | x−4/9=5/9 | | -7m=-4-9m | | 13x+6=2x+29 | | 3x+5(x+3)=-3+5x+48 | | -13.7=-5.3+3z | | x+5•(-2)+6=21 | | -6x-3=3x+4 | | -8x+15-6=-3x-11 | | 18-15x-2x=-83 | | 7x+24=-40 | | 20=3x/3+4/3 | | 20=(3x/3+4/3) | | 9x-7=10x=11 | | (2-4x)^2+20x=45 | | x^2=-841 |